Failure analysis of a safety equipment exposed to EAF environment. (January 2019) - Lanzutti, A.; Magnan, M.; Maschio, S.; Fedrizzi, L.
Abstract: The aim of this work was to determine the causes of failure of a safety system for the inspection of a crane used to load an Electric Arc Furnace (EAF). This system is composed of an assembly of cords and tensioners where the technicians are hooked in order to perform the crane system maintenance in safety conditions. This system, made of AISI 316 stainless steel, failed after few service months. In this work, the causes of failure have been investigated by means of microstructural and morphological characterizations of the failed components. In particular, a morphological and chemical analysis has been firstly performed by SEM + EDXS. Later on, a deep microstructural investigation of the failed components was performed in order to highlight possible weak points in the materials microstructure. The analyses showed that the components underwent to a severe Stress Corrosion Cracking (SCC) stimulated by the presence, in the working environment, of atmospheric condenses together with high chlorides containing EAF dusts. Highlights: The failure analysis of a safety system exposed to EAF dust has been performed; The components showed stress corrosion like cracks; Atmospheric condenses together with EAF dust stimulated a stress corrosion cracking mechanism; The EAF dusts contained a high chlorides amount.